RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP PUPUK CAIR SUPER BIONIK PADA PEMBIBITAN UTAMA (Main Nursery) - Yuza Defitri; Nasamsir Nasamsir; Ramadhani Siahaan (Universitas Batanghari, 2022)
This research was conducted at the Oil Palm Plantation of PT. Inti Indosawit Subur (PT.IIS), Tanjung Benanak, Merlung, Tanjung Jabung Barat from 20 January to 20 March 2021. This study aims to determine the response of oil palm seedling growth to super bionic liquid fertilizer at certain concentrations in the main nursery. This study used a completely randomized design (CRD) with super bionic liquid fertilizer treatment consisting of 5 levels, namely; s0 = control, s1 = 3 cc liter-1 super bionic liquid fertilizer per seedling, s2 = 6 cc liter-1 super bionic liquid fertilizer per seedling, s3 = 9 cc liter-1 super bionic liquid fertilizer per seedling, and s4 = 12 cc liter-1 super bionic liquid fertilizer per seedling. Parameters observed were plant height (cm), stem diameter (cm), shoot dry weight (g), root dry weight (g), and root-shoot ratio at 8 WAP. The research data were analyzed using analysis of variance, if it had a significant effect, then continued with Duncan's Multiple Distance Test (DNMRT) at the 5% level. The results showed that the application of super bionic liquid fertilizer had a significant effect on stem diameter, shoot dry weight, root dry weight and had no significant effect on plant height and root-shoot ratio. The application of super bionic liquid fertilizer with a concentration of 9 cc liter-1 resulted in an increase in plant height of 15.38%, stem diameter 23.78%, shoot dry weight 100%, root dry weight 71.56%, and root-shoot ratio 6.88. % compared to without super bionic liquid fertilizer (control).Keywords ; super bionic liquid fertilizer, palm oil